PERLINDUNGAN TERHADAP KESEHATAN MASYARAKAT MISKIN DI INDONESIA - Nugrahaningsih, Widi; Utami, Dytia; Hikmatululiya, Dysa; Aswari, Ayuk Dian (TIN: Terapan Informatika Nusantara, 2020)
Poverty is a phenomenon where an individual cannot fulfill his daily needs. Health is an important aspect for every individual because health is one of the needs that play an active role in daily life. health must always be a concern for every individual. While in Indonesia the rural poverty rate continues to increase, therefore the objectives to be achieved in this study are 1) knowing the cause of the continued increase in poverty 2) knowing the importance of reducing poverty 3) explaining the importance of protecting health for each individual without having to think about costs. this type of research is qualitative, describing, and using secondary data, in analyzing the data. The results of the study show that poverty continues to increase because the population continues to increase resulting in lack of employment, poverty rates can decrease if there is a cooperation between the community and the government, the government guarantees the health of its people with providing health insurance